EVALUATING THE STRENGTHS AND LIMITATIONS OF CHATGPT-GENERATED TRANSLATIONS IN ACADEMIC POST-EDITING WORKFLOWS - Brahmana, Christanta Rejuna Phanes S; Sofyan, Rudy; Mono, Umar (Universitas Islam Sumatera Utara (UISU), 2025)
This study evaluates the strengths and limitations of ChatGPT-generated translations in academic post-editing workflows. The research highlights ChatGPT's ability to enhance translation efficiency by producing grammatically precise and structurally sound drafts, enabling post-editors to focus on higher-level refinements like coherence and contextual accuracy. While the tool demonstrates significant advantages in improving workflow efficiency and adapting texts to academic conventions, it faces challenges in addressing cultural nuances and idiomatic expressions, particularly in underrepresented languages such as Indonesian. The study suggests potential improvements, including expanding training datasets and incorporating advanced contextual understanding features, to maximize ChatGPT's utility. Ultimately, the findings emphasize the importance of combining AI capabilities with human expertise to ensure high-quality and culturally sensitive academic translations. Future research should focus on refining AI tools to meet the diverse needs of global academic communication.